Pelatihan Pengenalan Aplikasi SPSS Dalam Pembelajaran Matematika - Syuhada Nasution, Ulfah; Dewi, Muthia; Tiara Manurung, Sari Bunga (PT. Bangun Harapan Bangsa, 2022)
In the learning process at MAS PMDU it is still passively included in mathematics learning, where mathematics learning has complicated calculations with three-dimensional graphics and images that require visual media in solving mathematical calculation problems and some students at the school think that statistical material is very complicated. especially in the data analysis process that requires precision and accuracy in the calculations. In this problem, service activities carried out at MAS PMDU, are exercises in using the SPSS application to overcome problems in learning mathematics, especially in statistical material. The method used in this activity is lecture and practice. This activity aims, as a lecturer's obligation to deal with the Tri Dharma of Higher Education, but also equips teachers and students with knowledge and techniques for presenting data. This activity is only limited to knowledge about descriptive statistical analysis which includes making frequency tables, how to analyze descriptive statistics and cross tabulation.